Android-Based Ramli Waste Bank Application in Samarinda City - Jainal Rahman; Muhammad Fahmi; Rizky Zakariyya Rasyad (STMIK Widya Cipta Dharma, 2026)
Household and plastic waste remain major challenges in environmental management in Indonesia, including in Samarinda City. One of the efforts to reduce waste volume while providing economic benefits to the community is through the RAMLI Sidodadi Waste Bank. However, data management and transaction recording at the waste bank are still carried out manually using passbooks, which may lead to recording errors, data loss, and inefficient customer services. Therefore, a technology-based solution is needed to improve the effectiveness and transparency of waste bank management. This study aims to develop an Android-based RAMLI Waste Bank application for Samarinda City that can facilitate data management and information access for both customers and administrators. The research employed a descriptive approach, with data collection techniques including literature studies, interviews, and observations. The system was developed using the Waterfall method, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The application was built using the Flutter framework, Dart programming language, and Firebase Realtime Database as the data storage platform. The application provides several features, including user login and registration, waste type information, waste bank location services, waste management educational content, point balance checking, transaction history, and user profile management. The development results indicate that the application improves transaction recording efficiency, facilitates real-time access to information, enhances data transparency, and reduces the risk of data loss. Therefore, the Android-based RAMLI Waste Bank application can serve as a digital solution that supports sustainable waste management while increasing community participation in environmental conservation and generating economic benefits through waste management activities.